2020
DOI: 10.1101/2020.06.26.173781
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The nucleus is a quality control center for non-imported mitochondrial proteins

Abstract: Mitochondrial import deficiency causes cellular stress due to the accumulation of non-imported mitochondrial precursor proteins. Despite the burden mis-localized mitochondrial precursors place on cells, our understanding of the systems that dispose of these proteins is incomplete. Here, we catalog the location and steady-state abundance of mitochondrial precursor proteins during mitochondrial impairment in S. cerevisiae. We find that a number of non-imported mitochondrial proteins localize to the nucleus, wher… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 42 publications
2
8
0
Order By: Relevance
“…1C, S1C). Consistent with previous reports, our data indicate that under normal conditions Oxa1 precursors associate with the ER surface only very transiently (Hansen et al, 2018;Shakya et al, 2020;, and that Ema19 has a role in regulating the amount or extent of this interaction.…”
Section: Cells Lacking Ema19 Show Higher Levels Of Non-imported Precusupporting
confidence: 92%
See 2 more Smart Citations
“…1C, S1C). Consistent with previous reports, our data indicate that under normal conditions Oxa1 precursors associate with the ER surface only very transiently (Hansen et al, 2018;Shakya et al, 2020;, and that Ema19 has a role in regulating the amount or extent of this interaction.…”
Section: Cells Lacking Ema19 Show Higher Levels Of Non-imported Precusupporting
confidence: 92%
“…A number of recent studies reported alternative approaches to follow the import reaction which resulted in surprising observations: (1) Ribosome profiling revealed that cytosolic chaperones and the signal recognition particle play crucial roles in distinguishing mitochondrial and secretory proteins already at very early steps in their synthesis (Schibich et al, 2016;Doring et al, 2017;Costa et al, 2018); (2) proximity labeling suggested that some mitochondrial proteins, in particular hydrophobic inner membrane proteins, explore the mitochondrial surface already during their synthesis (Jan et al, 2014;Williams et al, 2014; Vardi-Oknin and Arava, 2019; Wang et al, 2019) and that, in vivo, many (if not most) mitochondrial surface proteins are in direct proximity to the ER (Hung et al, 2017;Cho et al, 2020); (3) systematic screens of GFP-tagged protein libraries showed that many mitochondrial proteins are prone to accumulate in non-mitochondrial locations under certain growth conditions, in particular on the ER and within the nucleus (Vitali et al, 2018;Backes et al, 2020;Saladi et al, 2020;Shakya et al, 2020;Xiao et al, 2020) and, maybe even more surprising, observed non-mitochondrial residents in mitochondria (Ruan et al, 2017;Bader et al, 2020); and (4) genetic screens reported a very close cooperation of the mitochondrial and ER surface in protein biogenesis (Kornmann et al, 2009;Papic et al, 2013;Okreglak and Walter, 2014;Gamerdinger et al, 2015;Wohlever et al, 2017;Hansen et al, 2018;Vitali et al, 2018;Dederer et al, 2019;Matsumoto et al, 2019). Thus, in vivo, the surfaces of the ER and of mitochondria apparently vividly cooperate to sort proteins to the correct intracellular location.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thereby, mitochondrial protein biogenesis directly depends on the cytosolic chaperone capacity. Presumably as a consequence of their strong tendency to sequester chaperones, the cytosolic accumulation of precursor proteins induces a sudden growth arrest and triggers the increased expression of components of the chaperone and proteasome system (Boos et al, 2019, Boos, Labbadia et al, 2020, Mårtensson, Priesnitz et al, 2019, Shakya, Barbeau et al, 2020, Wang & Chen, 2015, Weidberg & Amon, 2018, Wrobel et al, 2015). Obviously, the post-translational import mode of mitochondrial proteins poses a threat for cellular proteostasis which is met by an adaptive network of cytosolic factors that can deal with unfolded precursors.…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondrial protein biogenesis strictly depends on the cytosolic chaperone capacity (Becker et al, 1996;Ben-Menachem et al, 2018;Deshaies et al, 1988;Doring et al, 2017;Hoseini et al, 2016;Stein et al, 2019;Terada et al, 1996). Presumably as a consequence of their strong tendency to sequester chaperones, precursor proteins accumulating in the cytosol induce a sudden growth arrest, trigger the heat shock response to increase components of the chaperone and proteasome system, and activate specific factors on the mitochondrial surface that clean off translocation intermediates (Boos et al, 2019;Boos et al, 2020;Martensson et al, 2019;Shakya et al, 2020;Wang and Chen, 2015;Weidberg and Amon, 2018;Wrobel et al, 2015).…”
Section: Introductionmentioning
confidence: 99%